Leadership Effectiveness in Unionized Work Environment: A Study on the Public Sector Organizations in Sri Lanka. (Global Business Management Review (GBMR), 2022)
Leadership effectiveness has been the central theme in most leadership research in early years of the 20th century. Behavior of the leader stands prominent as a determinant of leadership effectiveness in organizations. Understanding of effective leadership requires understanding both transactional nature of leadership as explained by existing theories, and the transformational influences of leadership. However, very few studies have been carried out on transformational and transactional leadership in unionized work context. Public sector organizations in Sri Lanka are characterized with high unionization of employees. Further, majority of the unions are politicized in terms of affiliation with main stream political parties. This situation has created a context where administrators of public sector organizations face context specific challenges and issues. With the common allegation leveled against the public sector organizations over their ineffectiveness, it is the leadership of these organizations which comes under criticism over their leadership effectiveness. However, no systematic study has been done to explore this issue in a managerial perspective. This paper proposes to examine the leadership effectiveness of the public sector organization under unionized work environment in Sri Lanka.